Modelagem das reservas internacionais ótimas no BRIC: tão heterogêneos, tão dependentes - Rebouças, Márcio Heber Medeiros (2015)
This study adds to discussion of theoretical and empirical literature, conceptually following Heller (1966), and aligning with the Calvo, Izquierdo e Loo-Kung (2012), and Alfaro e Kanczuk (2007; 2014), when analyzing international reserves countries that make up BRIC, for period 1997-2013, with a view to involving optimal level of reserves to a management tool protection (buffers) of public assets, which act as a buffer before balance of payments imbalances , due to crises and sudden stops, given previous evidence of contagion and financial integration in this block. Interest in BRIC is grounded in fact that next fifty years, these nations are likely to become major forces in the world economy. Following methodologically Frenkel e Jovanić (1981), we applied model titled buffer stock in time series of stores, and innovation and relevance in work due to consideration of likely significant cross effects of conditional volatilities and their bloc spreads, through a vector error correction model (VEC). It also appears that under application of econometric model, study findings show important role played by volatility of Brazilian and Russian stocks, as well as Chinese spread in explaining reserve management in some of other BRIC, which reflects adoption of any conservative or daring attitudes on the part of policy makers members of the bloc.